Whether sharing economy creates social value?. Issue 3 (19th June 2019) - Cui, Miao; Aziz, Sitara
Abstract : Purpose: The purpose of this paper is to look at the insights of the value of the society influenced by sharing economy (SE). The study focused on both the benefits and flaws of SE by using the case of renowned SE platform "Uber" to come up with a holistic perspective of these effects from both the facets. Design/methodology/approach: This study collects data from demand and supply side using interview and questionnaire. Then the grounded theory is adopted to analyze interview data and come up with six major research constructs. Further, quantitative analyses methods are applied on questionnaires to test "whether sharing economy creates social value" and to approximately estimate the extent to which sharing is economy influencing social value. Findings: Findings suggested that, when only drivers were inquired about positive and negative effects of SE, positive effects were dominant. Also, when passengers were asked their opinion was also in favor of positive effects. From quantitative data analysis, the major factor significantly influencing the sustainability of the SE was "efficiency." "Security issues and regulatory issues" were the prime negative factors, though again there was not enough statistical evidence to validate their significance. The authors hereby conclude that the positive contribution of SE is more, and it is increasing the values of the society. And the positive effects were twice significant than the negative effects. Originality/value: Theoretically, the study contributes to finding both the helpful and harmful effects of SE on the values of the society. Practically, it suggests that governments should allow growth of SE under proper regulations. And car-sharing companies should focus on solving the security issues and regulatory issues.